Oncogene-induced senescence: a potential breakpoint mechanism against malignant transformation in plasma cell disorders - Giesen, Nicola; Ellert, Elena; Xu, Jing; Hillengaß, Jens; Leichsenring, Jonas; Stenzinger, Albrecht; Goldschmidt, Hartmut; Andrulis, Mindaugas; Raab, Marc-Steffen (Leukemia and lymphoma, 2018)
Oncogene-induced senescence (OIS) is a cellular tumor-suppressive mechanism present in several premalignant conditions. Here, we analyze the possible impact of OIS on malignant transformation in plasma cell disorders. Tumor samples from 125 patients with different disease stages were analyzed immunohistochemically for expression of senescence markers. Protein expression of cyclin-dependent kinase inhibitor p21Cip1/Waf1 was significantly higher in smoldering multiple myeloma (SMM) compared to monoclonal gammopathy of undetermined significance (MGUS) (p = .02) or symptomatic multiple myeloma (MM) (p = .005). SMM plasma cells expressing p21Cip1/Waf1 were negative for Ki67, consistent with senescence. While p27Kip1 was highly expressed in healthy controls, MGUS and SMM, expression decreased significantly in MM (p = .02). SMM plasma cells displayed a mutually exclusive expression of p21Cip1/Waf1/p27Kip1 suggesting compensatory mechanisms of senescence. In conclusion, we found markers of cellular senescence differentially expressed in SMM compared to MGUS and MM supporting the hypothesis of OIS as a breakpoint mechanism against malignant transformation in plasma cell disorders.
Gesehen am 26.02.2020